Efeitos de diferentes níveis de restrição alimentar sobre características do líquido ruminal de caprinos - Souza, Francisco Jocelho Alexandre de (2018)
Goat farming is a widespread activity in the Northeast of Brazil, where the semiextensive and extensive breeding system predominates. The difficulty in evaluating the quality and quantity of ingested volumes makes it difficult to determine the nutritional status of the animals raised in these systems. The evaluation of ruminal fluid is a useful tool to identify deficiencies and metabolic diseases, but it is still little explored in this species. 25 castrated goats with 6 to 7 months of age were kept in collective pens and underwent adaptation period where they received bulky and concentrated food in addition to water and mineral salt. The experimental period was 72 days, and the animals were divided into 5 groups of 5 animals and submitted to isoproteic / hypoenegetic and isoenergetic / hypoprotein food restriction at different levels. The ruminal liquid samples were collected 7 times over the experimental period using a semi-flexible gas-gastric probe approximately 1.5 m long and 12 mm outside diameter, lubricated with vegetable oil. The variables measured were the pH, the reduction time to methylene blue (RAM), the sedimentation and flotation time (TAS) and the total titratable acidity (ATT) and the number of protozoa in the ruminal fluid. features. The hypoproteic / isoenergetic food restriction at 20 and 40%, hypoenergetic / isoprotein levels at the 20 and 40% levels and hypoenergetic / hypoproteic levels at the 30% level promoted alterations in ADR, TAS, ATT and in the number of protozoa in the characteristics of the liquid rumen growth of goats reared in confinement for 42 days, however, these changes were not able to cause damage to the rumen activities, since the values found were within the ruminant standard